ANALISIS PROGRAM EVALUATION REVIEW TECHNIQUE (PERT) DALAM PROSES CREATE INVOICE IMPORT OCEAN - Tito Warsito; Riki Alfandra (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
PT. DHL Global Forwarding Indonesia is a freight forwarding company that has imports and exports activities. This research discussed about Custom Clearance Department that has not had the time limit for creating invoice (to bill the customer) and has no time limit in processing the import’s documents which affect the company’s income in 2013. Using Program Evaluation Review Technique (PERT), the company could find out the time limit to create invoice by identifying every activities in creating invoice. Based on the analysis, invoice could be processed in four days. Using PERT could also help the company to define other activities done at the same time when processing the invoice. It is expected that the company could save time. After applying the suggestion in this research, hopefully the company could get more benefit.